Hubungan Interaksi Edukatif Terhadap Minat Belajar Siswa Kelas X pada Mata Pelajaran PAI di SMK N 1 Kinali - Amelia Amelia; Deswalantri Deswalantri; Mustafa Mustafa; Ulva Rahmi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Researchers found in the field, students lacked focus in learning because the learning process was still teacher-centered, students played around and told stories while the teacher was explaining, students lacked the courage to ask questions and express opinions, there were still students who were late for class. during PAI subjects. So the problem discussed in this research is the relationship between educational interactions and students' interest in learning at SMK N 1 Kinali. The aim of this research is to find out how much educational interaction has a relationship with students' interest in learning at SMK N 1 Kinali. This research method is a correlation method with a quantitative descriptive approach. The population in this study was all class X students, totaling 413 students. Determining the number of samples used a random sampling technique using the Slovin formula, so that the sample obtained was 80 class X students. The data collection technique in this research was using a questionnaire technique. Before testing the hypothesis, the researcher first carried out prerequisite tests in the form of normality tests and linearity tests. Then continue with the hypothesis test using the product moment correlation test. The results of the research show that there is a relationship between educational interactions and the interest in learning of class X students in PAI subjects at SMK N 1 Kinali. The relationship between the two variables is classified as sufficient with a correlation value of 0.661. These results show that (0.661) > (0.219). So it was rejected and accepted, so it can be interpreted that there is a relationship between educational interactions and the interest in learning of class X students in PAI subjects at SMK N 1 Kinali.